2016
DOI: 10.1007/s11356-016-8128-5
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in Tubifex tubifex for the metalaxyl and metalaxyl-M toxicity assessment in artificial sediment

Abstract: Efficacy and potential environmental risks should be considered when applying enantiopure pesticides. In this study, Tubifex tubifex and its oxidative stress biomarkers were assessed for the toxicity of metalaxyl and metalaxyl-M in sediment. The toxicity assessment was conducted with artificial sediment and reconstituted water. Five test concentrations (from 0 to 100 mg/kg) were set for the short-term (4 days) exposure. The long-term (28 days) exposure was conducted with the environmental concentration (from 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The fungicides metalaxyl and azoxystrobin correlated negatively with LPO. Regarding metalaxyl, no studies on its effect on sh LPO were found, however, a test carried out on Tubifex exposed to this fungicide showed that lipid peroxidation was increased, but only after three weeks of exposure (Di et al 2017). At earlier times, this biomarker was at the level of controls and that delayed effect was related to a saturation of the antioxidant systems.…”
Section: Discussionmentioning
confidence: 98%
“…The fungicides metalaxyl and azoxystrobin correlated negatively with LPO. Regarding metalaxyl, no studies on its effect on sh LPO were found, however, a test carried out on Tubifex exposed to this fungicide showed that lipid peroxidation was increased, but only after three weeks of exposure (Di et al 2017). At earlier times, this biomarker was at the level of controls and that delayed effect was related to a saturation of the antioxidant systems.…”
Section: Discussionmentioning
confidence: 98%
“…Due to the double-phase life mode, it plays an essential role in the aquatic ecosystem. They live in water and sediment [18]. The Tubifex ingests sediment particles and feeds on fine organic matter [19].…”
Section: Introductionmentioning
confidence: 99%
“…Tubifex , as a typical aquatic benthos that lives at the sediment–water interface, can be exposed to environmental pollutants through sediments, porewater and water columns, ingestion, and epidermal contact (Arendarczyk et al 2014; Di et al 2016b). Tubifex is considered ecologically relevant because of its wide distribution and frequent domination of the macrobiotic community in freshwater habitats (Mosleh et al 2005a; Di et al 2013, 2014).…”
Section: Introductionmentioning
confidence: 99%